Effect of treadmill exercise on the liver, kidney health, and serum IL-10 levels in high-fat diet-induced obese male Wistar rats - Samreen M. Sheik, H. Madhukar Mallya, Deepak Nayak Manel, Karkala Sreedhara Ranganath Pai, Vani Lakshmi Ramesh Iyer, Varashree Bolar Suryakanth, Revathi P. Shenoy (Journal of Applied Pharmaceutical Science, 2024)
This study investigated the impact of treadmill exercise on liver and kidney health in obese rats induced by a high-fat diet (HFD), alongside serum IL-10 levels. Rats were divided into normal control, HFD, HFD with atorvastatin, and HFD with exercise groups. Obesity was induced over 11 months via the HFD, while the exercise group underwent treadmill training three times per week for 90 days. Parameters measured included body weight, lipid profile, liver and kidney function tests, rat interleukine-10, and histopathology of the liver and kidney. Significant increases in body weight, lipid profile, and liver and kidney function tests, alongside decreased IL-10 levels, were observed in the HFD groups, indicating obesity-associated complications. After 90 days of exercise, significant reductions in body weight and lipid profile, alongside improved liver and kidney functions were noted, accompanied by increased IL-10 expression. The exercise group exhibited occasional liver micro vesicular fat droplets but an otherwise healthy liver and kidney appearance. Treadmill exercise demonstrated beneficial effects on liver and kidney health in male obese rats with HFD-induced obesity, primarily through the amelioration of IL-10 levels.
Keywords: Exercise, high-fat diet, IL-10, kidney, liver